An empirical study of emotional labor on customer loyalty intentions with mediating role of perceived service quality in banking sector - Muhammad Kashif, .; Mohd Hanafiah, Ahmad; Ali Khan, Muhammad Waris (Penerbit Universiti Malaysia Pahang, 2022)
The purpose of the study is to investigate the relationship between emotional labor and customer loyalty intentions. Investigating the mediating role of perceived service quality between the above variables is another objective of the study. The theoretical model of the effect of employee emotional labor on customer loyalty intentions having mediation of perceived service quality has been developed and tested. Causal research design on quantitative collected data provided support for the hypotheses from a sample of 350 bank customers in Malakand division KP, Pakistan. The results showed that employee emotional labor dimensions such as deep acting and Surface acting differentially affect customers' loyalty intentions. Furthermore, the effect of Deep acting on customer loyalty intentions is more than the effect of Surface acting. Researcher also investigate the potential mediating effect of perceived service quality on the relationship between emotional labor and customer loyalty intentions and find good support for such an effort from results.